Human capital externalities in Western Germany - Daniel F. Heuermann (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2009)
The paper sheds light on the impact of local human capital endowments on individual wages in Western Germany. Using panel data it shows that regional wage differentials are partly attributable to localized human capital externalities arising from the regional share of highly qualified workers. Employing the regional number of public schools and of students as instrumental variables, the paper shows that human capital externalities are underestimated in ordinary panel regressions for highly qualified workers due to supply shifts of workers of different skills. An analysis by sector reveals that human capital externalities are more pronounced in manufacturing than in the service sector. We find indication that highly qualified workers benefit from intraindustry knowledge spillovers, while non-highly qualified workers profit from pecuniary externalities between industries. Our findings are stable among a variety of indicators of regional human capital and robust to the inclusion of other sources of increasing returns, as well as wage curve, price level, and amenity effects.
Keywords: D62; D83; J24; J31; O15; 330; Human Capital Externalities; Agglomeration; Urban Wage Premium; Humankapital; Externer Effekt; Regionale Lohnstruktur; Alte Bundesländer; Deutschland